Optimizing provincial tax compliance: Implementing good corporate governance pillars - Aji, Anggit Kuncoro; Permadana, Ilham; Firmansyah, Amrie (Educoretax, 2024)
Tax revenue in the province is still low, even though the central government has handed over the tax base to the regions for more than 20 years. The concept of GCG can improve performance and tax revenue in the regions. This study examines the relationship of each pillar of Good Corporate Governance (GCG) to tax compliance and determines the types of GCG pillars that can be prioritized for implementation in a local government agency. This study uses the regional financial management transparency index (ITPAD) as an indicator of the transparency pillar, the fiscal independence index (IKF) as an indicator of the independence pillar, and financial statement audit opinion for the accountability and responsibility pillars. Finally, the Gini ratio is an indicator of fairness. The research sample was taken from all 34 provinces in Indonesia. Secondary data is sourced from publications, books, web pages, and previous research from 2016 to 2020. This period was chosen to exclude data from the COVID-19 pandemic era in Indonesia. The analysis method is panel data multiple linear regression with a random effect model. The results showed that fiscal independence and transparency of a region's budget management positively influence public tax compliance in a provincial area in Indonesia, while the opinion of financial statements and the Gini ratio have no influence. This study implies that to improve public tax compliance in a provincial area in Indonesia, and local governments can prioritize the implementation of the transparency and independence pillars achieved by increasing the ITPAD and IKF scores in their regions. The Ministry of Home Affairs can also encourage regions to enhance transparency and independence by improving ITPAD and IKF so that tax revenue in the regions can increase.